Governance, political rights, and Climate Justice: the prophylactic duty of international organizations in the COP 30 era (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
It proposes preventative duties for international organizations in the era of COP-30, arguing that the absence of equitable political participation constitutes a form of structural climate injustice that needs to be combated.(Received: September 2025 | Accepted: November 2025)
Keywords: International Organizations; Preventive Duty; Climate Injustice; COP-30; Political Participation